Relationship between work engagement and leadership in the bakery industry in Piura, Peru - Farfan Franco, Melissa Tatiana (2024)
Using a quantitative, non-experimental, cross-sectional research design, this study analyzed the relationship between leadership styles based on the Full-Range Model and work engagement in the bakery industry in the city of Piura in 2022. A sample of 60 workers were administered the Castro Solano et al. (2004) Leadership Styles Questionnaire (CELID) and the Utrecht Work Engagement Scale (UWES). The results revealed a strong correlation between leadership styles and work engagement, highlighting the influence of the motivational leader's role in guiding the rewards and benefits that enable motivated, committed and energetic employees to engage in their work. Specifically, transformational leadership and transactional leadership were found to have a positive impact on work engagement.